Development of Mobile Dua and Zikr for Hajj (MDZ4H) - Ahmed Sheikh Abdullah Al-Aidaroos; Abdul Nasir Zulkifli; Ruzinoor Che Mat (Institute of Advanced Engineering and Science, 2013)
In the last decade, the number of mobile phone users has increased dramatically. Nowadays, mobile phone has become part of people’s life. Today’s mobile phones provide not just voice call and messaging services, but plethora of other services. This research is about the utilization of mobile phone for dua and zikr for Hajj. The main aim of this research is to develop a mobile Dua and Zikr application to help Hajj pilgrims to recite them while performing all the Hajj, Umrah and Ziarah rituals. At the moment, this research focuses on developing the application on Android platform. In developing the application, all the required Dua and Zikr have to be gathered, compiled and verified before the prototype could be developed using J2ME. The prototype consists of text and audio files of the recited Dua and Zikr in Arabic as well as the translations in Malay. The prototype has been proven to be useful in helping the pilgrims to easily and conveniently recite the Dua and Zikr towards achieving Hajj Mabrur. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2509